1998
DOI: 10.1136/jnnp.64.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography in asymptomatic gene carriers of Machado-Joseph disease

Abstract: Objectives-The metabolic changes in the brain of symptomatic subjects aVected with Machado-Joseph disease have been previously documented using PET with fluorine-18-fluorodeoxyglucose (FDG). The aim of this study was to evaluate these changes in asymptomatic MachadoJoseph disease gene carriers. Methods-Seven asymptomatic MachadoJoseph disease gene carriers, identified using a molecular test, and 10 normal control subjects were recruited for PET studies using FDG. Regional uptake ratios of FDG were calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 20 publications
1
29
1
1
Order By: Relevance
“…It is intriguing to observe that the cerebellar metabolism did not correlate with ICARS or subscores within the patient group, but significant differences were noticed if healthy controls were included. In previous PET studies we have observed cerebellar hypometabolism in asymptomatic SCA2 and SCA3 gene carriers [11,21]. Results from this study demonstrating that the cerebellar hypometabolism does not necessarily correlate with the clinical severity of ataxia may explain why metabolic differences were observed more extensively between SCA patients and healthy controls, but not within the group of patients.…”
Section: Discussioncontrasting
confidence: 39%
“…It is intriguing to observe that the cerebellar metabolism did not correlate with ICARS or subscores within the patient group, but significant differences were noticed if healthy controls were included. In previous PET studies we have observed cerebellar hypometabolism in asymptomatic SCA2 and SCA3 gene carriers [11,21]. Results from this study demonstrating that the cerebellar hypometabolism does not necessarily correlate with the clinical severity of ataxia may explain why metabolic differences were observed more extensively between SCA patients and healthy controls, but not within the group of patients.…”
Section: Discussioncontrasting
confidence: 39%
“…PET and SPECT studies enable functional analyses beyond structural defects. F18-deoxyglucose PET detected altered glucose utilisation in cerebellum, brainstem, and cerebral cortex already in asymptomatic mutation carriers and thus demonstrated early presymptomatic changes in SCA3 (44). Dopamine transporter PET demonstrated decreased binding in the striatum similar to Parkinson's disease, but without significant asymmetry matching pathoanatomic findings of severe degeneration of the substantia nigra (45,46).…”
Section: Clinical Features Of Sca3 and Neuroimagingmentioning
confidence: 88%
“…Several nuclear imaging studies indicate involvement of various brain areas throughout the disease course in SCA3 (table e-3). [31][32][33][34][35] In patients with manifest SCA3, significantly reduced glucose metabolism has been reported in cerebellar hemispheres, vermis, occipital cortex, and brainstem. 31 Additionally, Taniwaki et al 33 found decreased glucose uptake in all cerebral lobes, putamen, and caudate nucleus.…”
mentioning
confidence: 99%